The ambiguous architecture of precarity: temporary protection, everyday living and migrant journeys of Syrian refugees. (2018) - Ilcan, Suzan; Rygiel, Kim; Baban, Feyzi
Millions of Syrians are currently displaced, living without adequate protection and struggling to access residency, rights and citizenship in the broader context of migration governance. Our understanding of migration governance through a focus on Syrian refugees in urban Turkey is telling for what it reveals about international and national commitments to refugee protection and the relations among precarity, refugee everyday living and migrant journeys. Drawing on and contributing to the critical migration and precarity scholarship, we focus on what we call the ambiguous architecture of precarity, where the objectives of providing protection to refugees simultaneously produce forms of precarity and ambiguities for them. We argue that three forms of precarity underscore the experiences of Syrian refugees in Turkey: precarity of status as revealed through the granting of temporary protection rather than legal refugee status; precarity of space as demonstrated through the challenges refugees experience in accessing services and with restricted mobility and; precarity of movement as developed through new border cooperation arrangements and through migrant journeys that are undertaken in search of greater protection and security.